A Systematic Review of Reviews of the Outcome of Severe Neglect in Underresourced Childcare Institutions. (July 2020) - Carr, Alan; Duff, Hollie; Craddock, Fiona
The aim of the systematic review described in this article was to determine the outcomes for individuals exposed to severe neglect in congregate care institutions such as orphanages. In this context, severe neglect refers to failure to meet children's basic physical, developmental, and emotional needs due to inadequate resources. In this systematic review of previous systematic reviews and meta-analyses, searches of 10 databases were conducted, 18 papers that met inclusion and exclusion criteria were selected for review, their quality was assessed, and data were extracted and synthesized. The 550 primary studies included in the 18 systematic reviews and meta-analyses were relatively well designed, allowing confidence to be placed in their results. Severe neglect was associated with a wide range of problems in the domains of physical development, cognitive development, attachment, and mental health. The severity of adverse outcomes was partly influenced by the duration and severity of deprivation and a constellation of risk and protective factors. Prevention policies should aim to eliminate large underresourced congregate care institutions for infants. In taking steps toward this, policies should aim to adequately resource congregate care institutions to meet children's developmental needs for nutrition, stimulation, and attachment to a stable primary caregiver with adequate parenting skills and training. Early placement in adoptive or foster families, with access to routine physical and mental health-care service available in developed countries, is the most viable effective intervention for child survivors of severe neglect.